Electron microscopy and biochemical analysis of native telomeric chromatin - Ahsan, Bilal (Nanyang Technological University, 2019)
Human telomeres are G-rich sequence repeats of DNA that span the terminal ends of chromosomes with an average length of about 10,000 base pairs. Telomeric DNA acts as a platform for the recruitment of a six protein-complex called shelterin. The shelterin complex protects chromosome ends from fusion and genome instability. Telomeric DNA is progressively shortened during each round of cell division, which leads to replicative senescence in somatic cells. For indefinite proliferation, approximately 85% of human cancer cells maintain their telomere length through reactivation of an enzyme called telomerase. The other 15% of human cancer cells use the Alternative Lengthening of Telomeres (ALT) pathway. Telomeres contain nucleosomes and a wealth of information exists on the functional role of telomere-binding proteins that regulate telomere length. However, little is known about the higher-order structure of telomeric chromatin in mammalian cells. Understanding the structure of telomeres will give insights into the interplay between nucleosomes and shelterin in the assembly of telomeric chromatin and regulating access to telomeric DNA, which ultimately regulates telomere length. The aim of this study is to obtain insight into the structural organisation of mammalian telomeric chromatin using electron microscopy (EM). To achieve this, three approaches were employed. First, the isolation of native telomeric chromatin from human and mouse cells. Second, in-vitro reconstitution of telomeric DNA with a shelterin protein called Telomeric Repeat-binding Factor 1 (TRF1). The presented data show that it is challenging to prepare samples suitable for EM analysis using these two approaches, due to protein loss during isolation or aggregation of the reconstituted material. The third approach used in this study and most successful was to apply correlative light and electron microscopy (CLEM) to visualize the ultrastructure of telomeres in-situ. For this experiment, I used a GFP-APEX2 tandem probe to selectively label TRF1 and telomeric chromatin in ALT cancer cells (human osteosarcoma U2OS cell line). CLEM and electron tomographic analysis shows that the telomeres closely associated with non-telomeric heterochromatin near the nuclear envelope. Inspection of electron micrographs reveals that ALT telomeres have a mean diameter of 345 nm and irregular shape. Furthermore, image analysis reveals that each telomere is composed of a complex network of interconnected fibres with a diameter that ranges from 10 nm to 35 nm.